Development of chromatographic method for applications in quality control and authenticity of distilled beverages - Nascimento, Hélio Oliveira do (2023)
Cachaça and whiskey distilled beverages are widely consumed in Brazil and their acceptance is closely related to quality control in their production. However, these beverages are frequent targets for adulteration, which alters the quality of these products and can lead to health problems for consumers. This work comprises three chapters where the first deals with a literature review on applications of the Solid-phase microextraction (SPME) technique in cachaça and whisky, the second was the development of a new methodology for the analysis of higher alcohols, n-butanol and total esters using gas chromatography coupled to barrier discharge ionization detector (GC-BID) and SPME via headspace (HS) as a sample preparation method for the analysis of 25 samples of cachaça and 26 of whiskeys, in the third chapter 16 samples of original and 14 counterfeit whiskeys were differentiated through principal component analysis (PCA) applied to data obtained by the HS-SPME-GC-BID method and aldehydes derivatized by 2,4-dinitrophenylhydrazine (2,4-DNPH) in high performance liquid chromatography coupled to diode array detector (HPLC-DAD). The results showed that the use of SPME in chromatographic analyzes of distilled beverages is a powerful tool that allows both the development of methods for quality control applications and the differentiation between original and counterfeit beverages.